A new Euro-Mediterranean cultural identity - Panebianco, Stefania (Frank Cass, 2003)
In this volume, concepts of democracy, civil society, human rights and dialogue among civilizations in the Mediterranean region are addressed in the context of the new Euro-Mediterranean Partnership.